Rancang Bangun High Voltage Generetor Sebagai Proses Plasma (Dielectric Barrier Dicharge) Untuk Pemurnian Air Payau - Hendi Matalata; Siti Umi Kalsum (Universitas Batanghari Jambi, 2023)
The need for clean water is currently the concern of many people, especially brackish water that occurs from land water discharge and the mixing of sea water with fresh water. Jambi Province in particular, there are several areas downstream of the river where the chemical/physical properties of water are blackish brown and are brackish water content, with this water content it is necessary to find a way to reduce the level in order to get water that is suitable for use by the community. The purpose of this study was to separate the content of brackish water using the plasma DBD (Dielectric Barrier Dicharge) method. Where the plasma concentration of DHF affects the level of brackish water related to Ph, TDS and Salinity. From the results of research on the DHF Plasma process for purification / separation of parameters of brackish water content from parameters of Ph, TDS and Salinity, there is a change or decrease in each of these parameters at each change in the length of the test time (5 minutes, 10 minutes and 15 minutes).